Participation and Evaluation of Prodamas Program in Kediri, East Java - Nekky Rahmiyati; Sri Andayani; Endang Indartuti (Enrichment : Journal of Management, 2020)
Implementation of local government as regulated in Law No.32 Th. 2004 and amended by Law No.23 of 2014 concerning Regional Government, prioritizing the implementation of decentralization which gives flexibility and most of the authority to the regions in implementing regional autonomy. Such discretion is in terms of the authority to determine and implement policies according to their own initiatives based on the aspirations of the community starting from planning, implementation, monitoring and evaluation. In Kediri City, there is a PRODAMAS program based on Kediri Mayor Regulation No.52 of 2014 concerning Guidelines for Implementing Community Empowerment Facilitation Programs. This study aims to determine the implementation of PRODAMAS Kediri City Government. As well as evaluating the PRODAMAS program of the Kediri City Government. The research method is descriptive qualitative research and uses a survey approach. The results showed that the implementation of 98.6% of the community knew and the remaining 1.4% did not know the PRODAMAS program. From community participation, it can be seen that the involvement of community infrastructure empowerment is 69.4%, involvement in economic development is 38.4%, involvement of social empowerment is 58.4%. While the impact of PRODAMAS was an increase in community infrastructure by 98.4%, an increase in human resource development by 66.2%, an increase in community social empowerment by 77.6%, an increase in poverty alleviation by 66.8%, creating employment by 54.8% and an increase in community participation by 83.6%.